REACTION OF THE CITOKINE PROFILE COMPOSITION OF THE ORAL FLUID ON DESINTOXICATION THERAPY IN CHILDREN WITH ACUTE ODONTOGENIC OSTEOMIELITIS OF THE LOWER JAW BODY - Доброскок, В.О.; V. A., (World of Medicine and Biology, 2016)
The paper presents the results of complex treatment of 37 children with acute odontogenic osteomyelitis of the mandibular body. Determined that due to the additional introduction in its composition of infusion therapy "Rheosorbilact" in the comparison group were observed in more pronounced tendency to normalization of levels of proinflammatory and anti-inflammatory interleukins in saliva, which indicates its clinical efficacy
Keywords: children; odontogenic osteomyelitis; interleukins; treatment